A Comment on the Economics of Labor Adjustment: Mind the Gap - Cooper, Russell; Willis, Jonathan L (American Economic Review, 2004)
We study the inferences about labor adjustment costs obtained by the gap methodology of Caballero and Engel [1993] and Caballero, Engel and Haltiwanger [1997]. In that approach, the policy function of a manufacturing plant is assumed to depend on the gap between a target and the current level of employment. We Þnd that their rejection of the quadratic cost of adjustment model, based upon evidence of nonlinear hazard functions, may not be justiÞed. Instead these nonlinearities may reßect difficulties measuring the gap. Thus it appears that the gap methodology, as currently employed, may be unable to identify the costs of labor adjustment. ∗We are grateful to seminar participants at Boston University, the University of British Columbia, University of Texas at Austin and the 2000 CMSG conference at McMaster University for comments and suggestions. Discussions with John Haltiwanger and Daniel Hamermesh were much appreciated. The authors thank the NSF for Þnancial support. The views expressed herein are solely those of the authors and do not necessarily reßect the views of the Federal Reserve Bank of Kansas City, the Federal Reserve Bank of Minneapolis or the Federal Reserve System.